2009
DOI: 10.1158/1541-7786.mcr-09-0064
|View full text |Cite
|
Sign up to set email alerts
|

Adaptor Protein Crk Induces Src-Dependent Activation of p38 MAPK in Regulation of Synovial Sarcoma Cell Proliferation

Abstract: The adaptor protein Crk mediates intracellular signaling related to cell motility and proliferation and is implicated in human tumorigenesis. The role of Crk in the growth of human sarcoma has remained unclear, however. The present study shows that Crk-induced activation of Src and subsequent signaling by p38 mitogen-activated protein kinase (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 47 publications
6
37
1
Order By: Relevance
“…In summary, our data in detail substantiate previous findings on the relevance of SRC in synovial sarcomas (40). For the first time, it is systematically shown that the SRC signaling network is commonly activated in synovial sarcomas and that targeting SRC results in substantial effects on tumor cell growth and motility.…”
Section: Discussionsupporting
confidence: 90%
“…In summary, our data in detail substantiate previous findings on the relevance of SRC in synovial sarcomas (40). For the first time, it is systematically shown that the SRC signaling network is commonly activated in synovial sarcomas and that targeting SRC results in substantial effects on tumor cell growth and motility.…”
Section: Discussionsupporting
confidence: 90%
“…Y221 in the C-SH3 of CrkII is a defined regulatory site [38], whereas CrkI does not contain this tyrosine residue, but holds much stronger transformative activity as compared with CrkII [30,31]. In contrast to previous studies that suggest that CrkI may function in a constitutively active form [39], our findings indicate that the phosphorylation status of CrkI can be altered by phosphatases like PTPN4 and some other unknown kinase(s). However, two questions remain unanswered.…”
Section: Discussioncontrasting
confidence: 79%
“…3) (Friedland et al, 2009;Schroer, 2014). Non-canonical TGF-β1 signaling through Src and p38 promotes the production of α-SMA in AVICs by the transcription factors myocardin related transcription factor (MRTF) and serum response factor (SRF) (Elberg et al, 2008;Hutcheson et al, 2012;Watanabe et al, 2009). FGF-2 signaling through FAK and ERK1/2 has been shown to prevent MyoFB differentiation in MEFs and to reverse TGF-β1-mediated expression of α-SMA (Greenberg et al, 2006;Kawai-Kowase et al, 2004;Schroer, 2014).…”
Section: Mechanosensors Of Stressmentioning
confidence: 99%